Improved Fine Motor Skills in Early Childhood Through the Traditional Game of Chess (Class Action Research in Kober Az-Zahra Ciamis) - Soni Samsu Rizal; Nia Nuraida; Taktik Kusmiati (CV Kalimasada Group, 2025)
This research is motivated by the problem of children lacking focus and being quiet that impact concentration, social interaction, and fine motor coordination. The traditional game of congklak is one solution because it is interactive, structured, and fun, so it can stimulate eye-hand coordination, concentration, and active participation of children. This research uses a qualitative approach with a case study method. The research subjects were 18 students at Kober Az-Zahra Ciamis. Data were collected through observation, interviews, and documentation using observation sheets and interview guidelines. The results showed that children's fine motor skills before the implementation of congklak were classified as low with an average score of 1.4 in the poor category. Children still had difficulty regulating finger movements, inserting congklak seeds, and maintaining concentration. After the implementation of the congklak game, the average score increased to 3.22 in the often able category. Children were more skilled in eye-hand coordination, more flexible in moving their fingers, and more focused on following rules. This proves that congklak is effective as an innovative learning medium to optimally stimulate the development of fine motor skills in early childhood.